2015
DOI: 10.3402/rlt.v23.27197
|View full text |Cite
|
Sign up to set email alerts
|

Using LectureTools to enhance student–instructor relations and student engagement in the large class

Abstract: Positive studentÁinstructor relationships are important for student engagement, motivation, retention and achievement. Yet, as class sizes grow, these relationships can be increasingly difficult to develop. This study explores LectureTools Á a webbased student response and learning platform that facilitates communication between instructors and students Á as a possible solution to this issue by analysing survey data collected from students in a second-year communication class at a large Canadian university. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Most of the studies carried out on student engagement originated from research in the United States (Shaw et al, 2015;Witkowski and Cornell, 2015). Although student engagement is valued among Chinese teachers (Zhu and Arnold, 2013;Wang, 2017) thanks to its high relationship with teaching success and improvement (Yin and Wang, 2016), just a few studies have been done in China to explore student commitment.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies carried out on student engagement originated from research in the United States (Shaw et al, 2015;Witkowski and Cornell, 2015). Although student engagement is valued among Chinese teachers (Zhu and Arnold, 2013;Wang, 2017) thanks to its high relationship with teaching success and improvement (Yin and Wang, 2016), just a few studies have been done in China to explore student commitment.…”
Section: Introductionmentioning
confidence: 99%
“…Some suggested uses of the ECHO360 ALP include taking attendance, analysing learner behaviour through learning analytics and for peer instruction (ECHO360, 2015). A previous study of an older version of ECHO360 ALP termed "Learning Tools" showed that there was enhanced student-teacher relationships and student engagement in large classes (Shaw et al, 2015). Time will tell whether similar benefits are also acquired due to its integration at this establishment but early feedback from students suggests that this will be the case.…”
Section: Resultsmentioning
confidence: 97%
“…Traditional lecture delivery is often didactic and unengaging for students, leading to less than ideal student learning and subsequent performance (Price and Kirkwood, 2013). The benefit of student engagement in their learning has been demonstrated over the past decade, and use of the ECHO 360 platform during lectures has the potential to promote this active learning concept (Shaw et al, 2015;Green and Whitburn, 2016). The use of ECHO 360 provided students with a collaborative and distinct learning environment to enhance student learning, engagement and improve lecture quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Generate out-of-class learning spaces (Bryant 2005, Azzawi and Dawson 2007, Qiu et al 2012, Kim 2013, Bati et al 2014, Shaw et al 2015),…”
Section: Factor 4-students Motivation and Engagementmentioning
confidence: 99%